ROLE OF ALTERNATE DISPUTE RESOLUTION IN ALLEVIATING JUDICIAL BURDEN IN PAKISTAN - Engr. Muhammad Idrees Yahya; Dr. Tansif Ur Rehman; Zunaira Eman Syed; Sumaima Adnan (International Journal of Contemporary Issues in Social Sciences, 2024)
The following article examines the critical role of alternate dispute resolution (ADR) mechanisms in alleviating and lowering the burden on the judiciary in Pakistan. The judiciary in Pakistan, like many other jurisdictions, is grappling with challenges such as case backlog, delays in justice delivery, and resource constraints. Against this backdrop, ADR methods emerge as pivotal tools offering potential solutions to expedite dispute resolution processes and enhance access to justice. Through an extensive review of literature, legal documents, and case studies, this study elucidates the diverse benefits of ADR, including its capacity to mitigate court congestion, reduce legal expenses, and provide amicable solutions tailored to the needs of disputing parties. Despite the evident advantages, the widespread adoption and effective implementation of ADR in Pakistan encounter obstacles ranging from a lack of awareness and legal infrastructure to entrenched cultural norms. The paper underscores the imperative for legislative reforms, capacity-building initiatives for legal practitioners and robust public awareness campaigns to foster the integration of ADR into the judicial framework. By addressing these challenges, policymakers can harness ADR’s transformative potential to fortify the legal system’s efficiency and efficacy, thereby advancing the cause of justice for all citizens in Pakistan.